Prevalence of resistance-associated substitutions (RAS) in hepatitis C virus in the Former Soviet Union countries - Sten H Vermund; Salima Davlidova; Syed Hani Abidi; Syed Ali; Robert Heimer; Aidana Mustafa; Dinara Begimbetova (BMJ Open Gastroenterology)
Objective The emergence of resistance-associated substitutions (RASs) poses a significant challenge to the effective treatment of hepatitis C virus (HCV) infection using direct-acting antivirals. This study’s objective was to observe the prevalence of HCV genotypes and RAS within the Former Soviet Union (FSU) countries.Methods We analysed 60 NS3, 313 NS5A and 1119 NS5B sequences of HCV deposited in open-access databases from 11 FSU countries for the prevalence of genotypes and the presence of RAS using the Geno2Pheno software.Results The following NS3 RASs were revealed through our analyses: 156P/S/T, 168del, 80K, 55A and 174S. The most prevalent NS5A RAS was 30K (12.69%) in genotype 3a, associated with resistance to daclatasvir, elbasvir and ledipasvir, followed by 62S (8.96% in genotype 3a), linked with resistance to daclatasvir, and 93H (3.95% and 6.72% in genotypes 1b and 3a, respectively), conferring resistance to daclatasvir, ombitasvir, elbasvir, ledipasvir and velpatasvir. The NS5B RASs found in this study were 451S and 556G, associated with resistance to dasabuvir.Conclusion The high prevalence of HCV genotypes 1b and 3a in the FSU region and the presence of specific RASs should be considered when determining the most effective treatment regimen for HCV-infected individuals in the FSU countries.